Performance-oriented design of thermal-activated building envelope based on multi-objective optimization: Method and application - Zhao, Tian; Zhuang, Zhi; Chang, Tianxin; Grunewald, John; Yu, Yao (Energy and buildings, 2025)
[Display omitted] •A systematic performance-oriented design method for the thermal-activated building envelope based on multi-objective optimization theory was proposed.•The performance-oriented design method comprises objective function, design variable, operation strategy, physical model, optimization algorithm, and evaluation decision.•A typical TABE with a capillary network was selected for case study.•Compared to the single-objective optimal solutions, the comprehensive optimal solutions obtained through multi-objective optimization achieve superior results.•The operation strategy of the source exerts a significant influence on the thermal performance of TABEs. The thermal-activated building envelope (TABE) offers potential for zero-energy buildings by leveraging low-grade natural energy and dynamically adapting to environmental changes. This study proposed a systematic performance-oriented design method for TABEs based on multi-objective optimization theory, mainly consisting of six parts: objective function, design variable, physical model, operation strategy, optimization algorithm, and evaluation decision. In addition, a typical TABE with a capillary network was selected for case study to demonstrate the effectiveness of this approach. By applying the proposed design method, optimal TABE configurations with capillary networks embedded in the inner plaster layer were obtained. Results show that multi-objective optimization effectively balances various objectives: maximizing annual thermal comfort hours, minimizing the annual heating and cooling loads, optimizing material costs, minimizing embodied carbon emissions, etc. Compared to single-objective optimization, the multi-objective approach achieves a superior balance across multiple criteria. For instance, a design solely optimized for maximizing annual thermal comfort hours or minimizing annual heating and cooling loads resulted in more than twice the material costs and embodied carbon emissions of those obtained through multi-objective optimization. Similarly, single-objective designs targeting lower material costs or embodied carbon emissions underperformed in energy efficiency. Compared to traditional ultra-low energy building envelopes, TABE offers enhanced energy efficiency, and provides at least 26.89% more comfort hours, 57.77% lower material costs, and nearly half the embodied carbon emissions. These results underscore that the proposed performance-oriented design method significantly enhances the overall functionality of TABEs, providing a robust approach for achieving sustainable and balanced building design.